2019
DOI: 10.1038/s41467-019-12487-w
|View full text |Cite
|
Sign up to set email alerts
|

Directing isomerization reactions of cumulenes with electric fields

Abstract: Electric fields have been proposed as having a distinct ability to catalyze chemical reactions through the stabilization of polar or ionic intermediate transition states. Although field-assisted catalysis is being researched, the ability to catalyze reactions in solution using electric fields remains elusive and the understanding of mechanisms of such catalysis is sparse. Here we show that an electric field can catalyze the cis-to-trans isomerization of [3]cumulene derivatives in solution, in a scanning tunnel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
165
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(166 citation statements)
references
References 33 publications
1
165
0
Order By: Relevance
“…18 Recently, STM tip induced electric field is shown to catalyze the cis-to -trans isomerization of cumulenes in solution. 19 A drawback of STM for studying electric-field effects is the inseparability of its control parameters. Since only two of the three factors (tip-sample distance, bias voltage and tunneling current) can be varied independently, it is not easy to identify system responses that are directly attributable to electric-field effects alone.…”
Section: Introductionmentioning
confidence: 99%
“…18 Recently, STM tip induced electric field is shown to catalyze the cis-to -trans isomerization of cumulenes in solution. 19 A drawback of STM for studying electric-field effects is the inseparability of its control parameters. Since only two of the three factors (tip-sample distance, bias voltage and tunneling current) can be varied independently, it is not easy to identify system responses that are directly attributable to electric-field effects alone.…”
Section: Introductionmentioning
confidence: 99%
“…44,[79][80][81] A seminal study by Shaik and co-workers demonstrated that not only can an EEF lower or raise the barrier for a Diels-Alder reaction when oriented in one direction or the other along the "reaction axis"-that is, the (approximate) axis along which electrons reorganize (on average) to make and break bonds-but an electric eld oriented perpendicular to the reaction axis can induce endo/exo selectivity. 82 The potential for EEFs to control chemical transformations has captured the curiosity of many groups [83][84][85][86][87][88][89][90][91][92] since Coote and co-workers experimentally demonstrated electrostatic catalysis of a Diels-Alder reaction in 2016. 93 For example, a recent experimental study demonstrated EEF-induced selective catalysis in a twostep reaction.…”
Section: External Electric Eldsmentioning
confidence: 99%
“…Although less stable than polyynes, [9]cumulenes have been characterized, and functionalized [3]-and [5]cumulenes have been measured in single-molecule junction experiments. 13,[19][20] The single-molecule conductance of odd-n cumulenes is expected to be higher than that of equivalent polyynes due to the smaller bond-length alternation, which narrows the HOMO-LUMO gap. 55 ELECTRONIC STRUCTURE.…”
Section: Odd-n Cumulenic Carbon Wiresmentioning
confidence: 99%